The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/su13073786
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Migration during Pyrolysis of Raw and Acid Leached Maize Straw

Abstract: Solid biofuel is considered as a possible substitute for coal in household heat production because of the available and sustainable raw materials, while NOx emissions from its combustion have become a serious problem. Nitrogen-containing compounds in pyrolysis products have important effects on the conversion of fuel-N into NOx-N. Understanding these converting pathways is important for the environmentally friendly use of biomass fuels. The nitrogen migration during pyrolysis of raw and acid leached maize stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…The result suggested that the introduction of H 2 strengthened the thermal cracking of more stable N–A types, which was in accordance with the results of Wang et al and Wei et al The yields of N-6 and N-5 showed a maximum value at 500 and 600 °C, respectively. This might be ascribed to the fact that N–A was converted into more N-6/N-5 through direct cyclization, dimerization, and rearrangement at lower temperatures and the secondary decomposition of N-5/N-6 was enhanced at higher temperatures. ,, At the temperatures from 600 to 800 °C, the N-5 yield decreased faster than N-6, which demonstrated that N-5 showed less thermal stability than N-6 at high temperatures . H radicals were active in the rupture of N-containing ring systems .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The result suggested that the introduction of H 2 strengthened the thermal cracking of more stable N–A types, which was in accordance with the results of Wang et al and Wei et al The yields of N-6 and N-5 showed a maximum value at 500 and 600 °C, respectively. This might be ascribed to the fact that N–A was converted into more N-6/N-5 through direct cyclization, dimerization, and rearrangement at lower temperatures and the secondary decomposition of N-5/N-6 was enhanced at higher temperatures. ,, At the temperatures from 600 to 800 °C, the N-5 yield decreased faster than N-6, which demonstrated that N-5 showed less thermal stability than N-6 at high temperatures . H radicals were active in the rupture of N-containing ring systems .…”
Section: Resultsmentioning
confidence: 99%
“…Besides, it was found that a H 2 -rich atmosphere produced less heterocyclic–N than an Ar atmosphere at the same temperature. This phenomenon could be explained by two possible reasons: ,,, (1) the H 2 -rich atmosphere suppressed the polymerization of amine–N into heterocyclic–N by deactivating the free radicals and (2) the combination of H 2 and high temperatures promoted the ring-opening reactions of heterocyclic–N, resulting in more NH 3 and HCN.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations